PERANCANGAN FASILITAS PELENGKAP DI AREA DESA BUDAYA KESIMAN KERTALANGU - Purwaadinata Cahyadi, Marcello Gede Audhy; Merta Yasa, I Gede Adi; Fitri Nur, Salwaa; Safira, Beby; Hany Putri, I Gst. Ayu Pt.; Dioga Adi Pramana, I Gusti Nyoman; Ajeg Karunia, Komang Tresna; Suarbawa, I Nyoman; Alvina, Jesslyn; Wikannanda, Ida Ayu Dwiaditi; Aryawan, Brenda Lee; Satria Angkasa, Made Pande Aji; et al. (Buletin Udayana Mengabdi; Vol 24 No 3 (2025): Buletin Udayana Mengabdi, 2024)
Kertalangu Cultural Village is one of the tourist destinations in the Kesiman Kertalangu Village area, East Denpasar. The area has a historical heritage, namely there is the World Peace Gong. Not long before, the Kertalangu Cultural Village created an educational tourist spot called TeBA Majalangu. The area has not been fully developed because there is still a lot of empty land around it and the building concept adapts sustainable and traditional architectural buildings that use natural materials. The design of complementary facilities carried out by the PPK ORMAWA HMA 2022 team this year will design parking areas, wantilan and glamping areas. The design location is in the TeBA Majalangu area where the design concept will involve one of the architects, namely Siandsain Architect and the Village Head of Kesiman Kertalangu. The design method covers several aspects, namely collecting data in the form of observations and interviews, designing the area and surrounding buildings and making working drawings and posters. The design of these complementary facilities is expected to be able to improve the image of a village that is friendly to children and visitors who will visit the TeBA Majalangu area. It is hoped that by designing these complementary facilities, the surrounding area will look more beautiful and will become one of the tourist destinations that must be visited. Keywords: Facility Planning, Kesiman Kertalangu Village, TeBA Majalangu, Cultural Village.